We showed Baltimore : the lacrosse revolution of the 1970s and Richie Moran's Big Red - Swezey, Christian (Three Hills, an imprint of Cornell University Press, 2022)
"The sport of lacrosse is older than baseball. And it underwent a transformation in the 1970s. Heavy, handmade wooden sticks were replaced by lighter, plastic ones; the NCAA instituted a playoff to determine national champions; Long Island began producing top players; and Cornell rose to the top of the sport"--